EFL TEACHERS’ ATTITUDES AND EXPERIENCES ON THE IMPLEMENTATION OF MULTILITERACIES - Ria Sujiati; Aswadi Jaya; Evi Rosmiyati; Noviati (Universitas PGRI Palembang, 2024)
The main problem in this research is: what are the elements that influence the attitudes and experiences of EFL teachers in implementing multiliteracy, and how can EFL teachers be used as role models for implementing multiliteracy in terms of their attitudes and experiences? The purpose of this research is to find out how the attitudes and experiences of teachers towards students during the learning process affect them and how multiliteracy can be applied during the teaching and learning process, whether it makes learning effective or vice versa. This research was carried out at SMP PGRI 1 of Palembang. This research was carried out using qualitative methods. First, the researcher made observations at school to find out how effective the teaching and learning process was in class, especially in English lessons. Furthermore, the researchers conducted interviews with the English teacher and distributed 20 questionnaires to 30 students in class VIII.4 in the even-numbered 2022/2023 academic year. Based on the findings from this study, the researcher concludes the results of the research analysis. And from the results of this analysis, the researchers concluded that 90% of SMP PGRI students liked English lessons and always got good motivation and role models from the teacher, meaning that the teacher could provide good motivation to students and always give a good attitude during the learning process. Students are also more active in the application of multiliteracy because there is good interaction between the teacher and students.